The obesity paradigm and the role of health services in obesity prevention: a grounded theory approach - Claire Pearce; Lucie Rychetnik; Andrew Wilson (BMC, 2021)
Abstract Background Health services have a clear role in the treatment of obesity and diseases linked to obesity but a less well-established role in prevention, particularly in hospital and community-based health services. Methods The aim of this research was to examine whether and how hospital and community-based health services incorporate adult obesity prevention into policy and practice. The case study setting was an Australian based health service. Grounded theory informed all aspects of the research including participant recruitment, data collection and data analysis. A systems approach guided the analysis of diverse perspectives, relationships and interconnections within the study context. Results The prevailing paradigm within the health service is that obesity is a matter of choice. This dominant perspective combined with a disease focused medical model overly simplifies the complex issue of obesity and reinforces the paradigm which treats obesity as a matter of individual responsibility. A focus on individual change hinders health services from playing an effective role in obesity prevention and leads to unintended consequences, including increasing stigma. Conclusions Health service responses to obesity and its prevention compound the negative elements associated with obesity for individuals and are ineffective in creating positive change at individual or a societal level. An alternative systems-level approach is needed to align health service responses with contemporary approaches that address obesity prevention as a complex problem.